Sensory analysis and brand influence on yogurt acceptance (Research, Society and Development, 2021)
The study aimed to evaluate the influence of sensory characteristics and the brand, on the acceptance of yogurt by the consumer. This is a descriptive experimental study, in which volunteers (untrained tasters) answered a questionnaire containing questions related to the consumption of yogurt and participated in two sessions of sensory analysis (blind and information tests) of two brands of strawberry flavoured yogurt, one of the brands being known in the national market (Yogurt A) and the other in the regional market (Yogurt B). The tasters evaluated the colour, aroma, flavour, texture and overall impression of the samples, using hedonic scale of 9 points. The evaluations were carried out in individual booths, under white light, with the samples coded with three digits and served at random. Statistical analyses were performed using SAS software version 9.0. All participants were consumers of yogurt and 90.4% preferred strawberry flavoured yogurt. Most participants reported consuming yogurt once (23.1%) twice (23.1%) times a week or fortnightly (23.1%). There was no significant difference between tests with brand A and B yogurts in terms of texture and overall impression. It was found that brand A positively influenced the acceptance of yogurt, according to the comparison of the results of the blind test and the test with information. It was concluded that the two brands of yogurts evaluated were well accepted by the tasters, with the influence of brand A on the acceptance of yogurts, which reveals the importance and the need for marketing investment for greater commercialization of brand B yogurt.